2018
DOI: 10.1007/s13201-018-0803-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variation in physicochemical parameters and heavy metals in Awash River, Ethiopia

Abstract: Awash River, one of the major rivers in Ethiopia which originate from the central highland area, crosses different extended agricultural farms as well as various industries which receives large effluents from different sources. Nineteen physicochemical parameters, as well as heavy metals (Fe, Zn, Cu, Pb, Cr, Cd and Ni), were quantified using atomic absorption spectroscopy in eight different sampling stations of Awash River. There was a significant spatial variation (p < 0.05) in average NO 3-N, NH 4-N, TN, BOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 40 publications
(29 reference statements)
4
39
3
Order By: Relevance
“…It is reported that iron is a major inorganic water quality problem and is mainly transported in groundwater in the reduced form as Fe2+ [59]. Amadi[60], Eliku and Leta[51] reported lower Fe concentrations (0.011 to 2.897 and 1.11 to 4.12 mg/L) in water from Sosiani river (Kenya) and Awash river (Ethiopia) than is reported in Nyabarongo and Nyabugogo rivers in this study. Elevated levels of Fe in water (12.6 to 15.51 mg/L) comparable to that reported in this study were reported in Mara river of Tanzania by Kihampa and Wenaty…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…It is reported that iron is a major inorganic water quality problem and is mainly transported in groundwater in the reduced form as Fe2+ [59]. Amadi[60], Eliku and Leta[51] reported lower Fe concentrations (0.011 to 2.897 and 1.11 to 4.12 mg/L) in water from Sosiani river (Kenya) and Awash river (Ethiopia) than is reported in Nyabarongo and Nyabugogo rivers in this study. Elevated levels of Fe in water (12.6 to 15.51 mg/L) comparable to that reported in this study were reported in Mara river of Tanzania by Kihampa and Wenaty…”
contrasting
confidence: 39%
“…High TDS affects the aesthetic quality of water, interfere with washing operations and can be corrosive to plumbing fixtures [47]. [50,51]. Excess amount of TN in water may lead to low levels of dissolved oxygen and negatively alter various plant life and organisms.…”
Section: Electrical Conductivity and Total Dissolved Solidsmentioning
confidence: 99%
“…Laboratory analyses of nineteen physico-chemical parameters were generally performed following standard protocols [10] [11]. Colour was measured using the platinum-cobalt standard method using HACH DR/2010 spectrometer [3].…”
Section: Physico-chemical Parameter Measurementsmentioning
confidence: 99%
“…This deterioration has been attributed to both natural processes such as weathering of underlying crustal materials, erosion, precipitation and anthropogenic activities which are triggered by climate change, agricultural land use, industrial and sewage effluent discharge [1] [2]. Anthropogenic activities are major contributors of pollutants to surface water resources in developing countries such as Uganda, the most important being urban sewage, agriculture and industrial effluents which are well known for nutrient loading and heavy metal pollution of water bodies [3] [4] [5]. Moreover, river water resources are important in promoting human development as they serve as domestic water sources; provide water for agriculture, industries and transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation